2016
DOI: 10.3892/mmr.2016.4770
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-451 inhibits neuroblastoma proliferation, invasion and migration by targeting macrophage migration inhibitory factor

Abstract: Neuroblastoma (NB) is the most prevalent type of extracranial solid tumour in young children. To improve current understanding of the mechanisms, which modulate cancer cell proliferation, invasion and migration, investigations have focused on microRNAs (miRs), a class of small non‑coding RNAs, which post‑transcriptionally regulate gene expression during various crucial cell processes. The present study aimed to investigate the role of miR‑451 in NB. Human NB tissue and adjacent normal tissue were surgically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
(32 reference statements)
1
18
0
Order By: Relevance
“…Both prior studies employed RNU6 as a reference. While hsa-miR-451a has been found to act as a tumor suppressor [64,65], it is also a marker of hemolysis [66] and thus we suggest that care should be employed to exclude samples with hemolysis before analysis. The miRNA ratio of hsa-miR-451a and hsa-miR-23a-3p has been employed by others [56,67] to monitor for sample hemolysis.…”
Section: Effect Of Reference Mirna Used To Normalize Resultsmentioning
confidence: 95%
“…Both prior studies employed RNU6 as a reference. While hsa-miR-451a has been found to act as a tumor suppressor [64,65], it is also a marker of hemolysis [66] and thus we suggest that care should be employed to exclude samples with hemolysis before analysis. The miRNA ratio of hsa-miR-451a and hsa-miR-23a-3p has been employed by others [56,67] to monitor for sample hemolysis.…”
Section: Effect Of Reference Mirna Used To Normalize Resultsmentioning
confidence: 95%
“…Liu et al have shown that the transfection of the SK-N-SH and GI-LA-N human NB cell lines with miR-451 reduced tumor proliferation, invasion, and migration, and that MIF was negatively regulated by miR-451 that directly targeted the 3 UTR of MIF mRNA in the NB cell lines [99]. Moreover, the overexpression of MIF counteracted the inhibitory action of miR-451 on NB cells growth, invasiveness, and migration, thus indicating that the anticancer activity of miR-451 may be due to the suppression of MIF expression [99].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Liu et al have shown that MIF was a direct target gene of miR-451, which was significantly downregulated in tumor tissue samples of NB patients [99]. Moreover, they found that the reduction in miR-451 was significantly associated with negative tumor features, such as higher TNM stage, larger carcinoma size, lower degree of differentiation, and higher presence of metastases [99]. Therefore, they suggested that the miR-451/MIF pathway could be a novel therapeutic target for NB patients [99].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…One hypothesis we would like to present is that expression of MIF in the migrating tNCC might favor DRG ganglionation via self-attraction. MIF is highly overexpressed in many types of malignant tumors and its level of upregulation has been correlated with the aggressiveness of the cancers (Chesney and Mitchell, 2015;Liu et al, 2016). Interestingly, neuroblastomas, which are of NCC origin, express high level of MIF (Zhou et al, 2008).…”
Section: Macrophage Migration Inhibitory Factor (Mif) and Neural Cresmentioning
confidence: 99%